International Education Exchanges and Intercultural Understanding Promoting Peace and Global Relations - Mathews-Aydinli, Julie (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
XIII, 184 p. 11 illus., 1 illus. in color.